Perubahan Status Kelembagaan pada Perguruan Tinggi Agama Islam dalam Menghadapi Tantangan dan Peluang Pendidikan Islam di Indonesia - M. Yusuf Aminuddin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2019)
Islamic education institutions as one of the open social institutions, and as agents of change need to pay attention to the demands of changing times. Changing institutional status is a demand for professional, high-quality education and offers many choices. Especially with the welcome flow of globalization and industry 4.0 which gave birth to a competitive and competitive environment. So that changes in Islamic education institutions are part of efforts to face challenges and capture opportunities for Islamic education. these changes require strong efforts by stakeholders in reviewing and evaluating change management, leadership, facilities, students, finance and the readiness of human resources is very influential in building Islamic education institutions.